1992
DOI: 10.1192/bjp.161.3.323
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Aberrations and Schizophrenia

Abstract: Chromosomal aberrations associated with schizophrenic disorders may suggest regions in which to focus a search for genes predisposing to schizophrenia by a linkage strategy. As for other genetic illnesses, chromosomal abnormalities may also provide useful tools for subsequent physical mapping, fine localisation, and isolation of important susceptibility genes. Identification of several chromosomal aberrations may be especially important, given the unknown pathophysiology, the paucity of known brain genes, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(17 citation statements)
references
References 56 publications
1
15
0
1
Order By: Relevance
“…Consistent with early reports of the association of schizophrenia with rare microscopically visible chromosomal abnormalities156 and the established association with 22q11.2 deletions,43,66,67,69 there is now substantial evidence for the importance of diverse rare structural variants in causing schizophrenia 3,5. These structural variants are mainly comprised of specific examples of large (eg, >500 kb) CNV that are consistently enriched in schizophrenia samples, and absent or extremely uncommon (ie, “rare”) in control populations.…”
Section: Schizophrenia In the Molecular Agesupporting
confidence: 89%
“…Consistent with early reports of the association of schizophrenia with rare microscopically visible chromosomal abnormalities156 and the established association with 22q11.2 deletions,43,66,67,69 there is now substantial evidence for the importance of diverse rare structural variants in causing schizophrenia 3,5. These structural variants are mainly comprised of specific examples of large (eg, >500 kb) CNV that are consistently enriched in schizophrenia samples, and absent or extremely uncommon (ie, “rare”) in control populations.…”
Section: Schizophrenia In the Molecular Agesupporting
confidence: 89%
“…The finding of fragile sites on chromosomes 3, 9, 17, 18, and 19 in schizophrenic patients is described in a review by Bassett (1992). Moreover, Garofalo et al (1992Garofalo et al ( , 1993 reported a significantly higher presence of rare fragile sites at chromosomal regions 9p21 and 10q21 in metaphase lymphocytes of schizophrenic patients than in the control group.…”
Section: Introductionmentioning
confidence: 90%
“…Many susceptibility loci for schizophrenia were identified. Significance levels for linkage to schizophrenia were obtained for chromosome regions 6p24-p22 [52], 1q21-q22 [43], 13q32-q34 [53], 10p14 [54], 10q25.3-q26.3 [55], 8p22-p21 [53,56], 6q21-q25 [57,58], 22q11-q12 [59,60] and 5q21-q33 [61,62]. A further susceptibility locus was identified on the short arm of chromosome 20 (20p) [63,64].…”
Section: Introductionmentioning
confidence: 99%